Conceptions on disability in public and private Higher Education institutions - Leite, Lúcia Pereira [UNESP]; Cabral, Leonardo Santos Amâncio; de Lacerd, Cristina Broglia Feitosa (FapUNIFESP (SciELO), 2023)
This article aims to study and analyze the conceptions of disability presented by 1763 university students. The Conceptions on Disability Intercultural Scale was applied to students at three universities in the State of São Paulo, two of which are public – federal and state – and one is private. Results were exposed to statistical processing, to compare the data obtained among the students in these different contexts and to analyze the relationships between the choice of positioning in certain variables, such as the area of expertise and/or academic training and age group. The results allow for a systematization of information in order to understand social, political and educational behaviors and cultures, which may indicate ways of overcoming discriminatory attitudes based on disability, and situate the university as an environment where the disability issue can be the subject of critical debates among future professionals
Concepciones sobre discapadicad en instituciones de Educación Superior publica y privada
Concepções sobre deficiência em instituições públicas e privadas da Educação Superior
Keywords: Conception; Higher Education; People with Disability; Public Policies